Peran Pustakawan di Perguruan Tinggi Sebagai Partner Riset dalam Pemenuhan Kebutuhan Informasi Pengguna - Harahap, Dwi Retno Syahfitri (Perpustakaan Universitas Gadjah Mada, 2024)
The role of librarians in higher education as research collaboration partners is a crucial aspect in fulfilling the function of libraries as information centers. This study aims to analyze and identify the role of librarians in higher education as research partners in meeting user information needs. Adopting a qualitative approach through literature study methods, this research investigates how librarians function not only as providers of information resources but also as active collaborators in the research process. In this context, librarians assist in information literacy training, mapping research themes, and providing and managing digital resources that meet current academic and research needs. The findings indicate that collaboration between librarians and researchers strengthens the knowledge infrastructure and enriches research resources, but also faces challenges such as limitations in librarians' research skills, the need for professional development, and funding issues. This study emphasizes the importance of developing librarians' skills in research and information technology to support effective academic and research activities, and highlights the strategic role of libraries in enhancing the quality and effectiveness of research in higher education.